Internet world guide to webcasting - Miles, Peggy 1959- (John Wiley & Sons, 1998)
Using the latest generation of Web technology, you can build your own "television" or "radio" network as an Internet Broadcaster. It's called "webcasting," and Fortune 500 companies use it today for a variety of purposes, including in-house education and training, infomercials, marketing campaigns, advertising, public relations, customer support, corporate communications, and more. Find out from international webcasting expert Peggy Miles how organizations worldwide are using webcasting to give them a powerful competitive edge, and how to make the technology work for you, too.